(untitled) (Nepalese Horticulture, 2025)
A field experiment was conducted from 2021 to 2023 at the Directorate of Agricultural Research, Khajura, Banke, to assess the effect of cultivars and planting dates on vegetative growth, crop duration, and yield attributes of Cavendish banana cultivars ‘Grand Naine’, ‘Williams’, and ‘Indonesian’. The experiment was laid out in a split-plot design, with three banana cultivars as the main plot factor and six planting dates as the sub-plot factor, replicated three times. The first planting was carried out on 15th May 2021, and subsequent plantings were done at two-month intervals over one year. Results indicated that planting dates significantly influenced vegetative growth, crop duration, and yield attributes, while variety had little effect. Among the planting dates, the 15th July planting recorded the highest values across key parameters: base circumference (70.77 cm), leaf area (12.11 m²), cumulative leaves (42.56), bunch length (110.11 cm), distance between the first and final hand (53.44 cm), and yield attributes such as number of hands (9.67), number of fingers per bunch (169.10), finger length (21.26 cm), finger girth (13.03 cm), finger weight (141.00 g), and bunch weight (20.85 kg). Although, early planting on 15th March or 15th May shorten the harvest duration, the yield potential was lower (45.38 t ha-1 for the 15th March planting and 53.26 t ha-1 for the 15th May planting) compared to the 15th July planting (64.37 t ha-1). This study suggests that the 15th July planting is optimal for maximizing banana growth and yield in the Western Terai region of Nepal.